Increased DHA Production in Seed Oil Using a Selective Lysophosphatidic Acid Acyltransferase - Shrestha, Pushkar; Hussain, Dawar; Mulder, Roger J.; Taylor, Matthew C.; Singh, Surinder P.; Petrie, James R.; Zhou, Xue-Rong (Frontiers in Plant Science, 2018)
Metabolic engineering of the omega-3 (ω3) long chain polyunsaturated fatty acid biosynthesis pathway has generated fish oil-like levels of pharmaceutically and nutritionally important docosahexaenoic acid (DHA) in plant seeds. However, the majority of DHA has been accumulated at the sn-1 and sn-3 positions of triacylglycerol (TAG) in these engineered seeds, leaving only a minor amount (~10%) at sn-2 position and indicating a strong discrimination (or, a very poor specificity) for DHA by seed lysophosphatidic acid acyltransferases (LPAATs), which mediate the acylation of sn-2 position of glycerol backbone. In order to increase the level of DHA at sn-2 position of TAG and to increase overall DHA level in seeds, we attempted to discover DHA-preferring LPAATs. Several lysophosphatidic acid acyltransferases (LPAATs) for acylation of the sn-2 position of the TAG glycerol backbone were investigated for substrate preference for DHA. In transiently expressing these LPAATs in Nicotiana benthamiana, a Mortierella alpina LPAAT had the highest substrate specificity for accumulating DHA onto oleoyl-lysophosphatidic acid (oleoyl-LPA), while the plant LPAATs tested showed lower preference for DHA. In a competition assay with a pool of four ω3 acyl-Coenzyme A (CoA) substrates involved in the DHA biosynthesis pathway, LPAATs from both M. alpina and Emiliana huxleyi showed a high preference for DHA-CoA acylation onto oleoyl-LPA. When docosahexaenoyl-LPA was used as the acyl receiver, M. alpina LPAAT also showed a high preference for DHA-CoA. Stable overexpression of M. alpina LPAAT in an Arabidopsis line that expressed the DHA biosynthesis pathway significantly increased both the total DHA levels and the distribution of DHA onto the sn-2 position of seed TAG. LC-MS analysis of the seed TAG species also confirmed that overexpression of M. alpina LPAAT increased di-DHA and tri-DHA TAGs, suggesting that the M. alpina LPAAT could enrich DHA at the TAG sn-2 position, leading to a metabolic engineering of oil seed for channeling DHA into the sn-2 position of TAG and to a higher DHA level.